Modeling the Influence of Green Investment Intention on Investment Behavior: An Extended Theory of Planned Behavior Approach - Priyo Priyantoro; Katherin Daniar (Green Publisher Indonesia, 2025)
The urgency of climate change and sustainability issues has highlighted the importance of green investment, particularly among young generations who are increasingly exposed to financial decisions through digital platforms. This study aims to examine the influence of attitude toward behavior, subjective norms, perceived behavioral control, and financial literacy on green investment intention, as well as the role of financial influencers as a moderating variable, and the subsequent impact on actual green investment behavior among Generation Z investors in East Java, Indonesia. Using an explanatory quantitative approach, data were collected from 400 valid respondents selected through purposive sampling, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that all four predictors—attitude toward behavior, subjective norms, perceived behavioral control, and financial literacy—have a positive and significant effect on green investment intention. Furthermore, green investment intention and perceived behavioral control are proven to significantly drive actual green investment behavior. The moderating test indicates that financial influencers only strengthen the relationship between attitude toward behavior and green investment intention, while their influence is insignificant on subjective norms, perceived behavioral control, and financial literacy. These findings contribute to the extension of the Theory of Planned Behavior by incorporating financial literacy and influencer effects into the model. The study provides theoretical implications for behavioral finance research and practical insights for policymakers, educational institutions, and financial regulators to design strategies that enhance sustainable investment literacy and foster long-term participation in green investment.